Adaptation strategies to climate change followed by the Murrah Buffalo Farmers of Haryana - Manjunath K V et al. (Indian Journal of Dairy Science, 2025)
Air temperature, humidity, wind velocity and solar radiation are the main climate variables that affect buffalo production in tropical climate. Adaptation is the adjustment in natural or human systems to a new or changing environment that exploits beneficial opportunities or mitigates negative effects. The Adaptation strategies are an imperative requisite in the current sceanrio to decrease the the negative impacts of climate change in order to maintain sustainable production. Therefore, the present study was undertaken to assess the adaptation strategies followed by the Murrah buffalo farmers to cope with the changing climatic conditions. The current study was carried out in Hisar, Jind and Rohtak districts of Haryana. From each district two blocks were selected randomly and from each block 4 villages were selected randomly, thus 24 villages from the 6 blocks.  From each village 15 farmers were selected randomly constituting a total sample size of 360 respondents. Primary data was collected from respondents through a well-structured interview schedule. Feeding during cooler parts of the day, use of concentrates for animal feed, providing chopped fodder, providing fresh and clean drinking water, wallowing/bathing, regular vaccination, shed hygiene, sowing improved varieties of crops and change in crop calendar were the most common followed adaptation strategies by the Murrah farmers to cope with the changing climatic conditions and minimize adverse impacts of climate change on their crop-livestock farming.